EFFECT OF DIFFERENTIATED SCIENCE INQUIRY ON ACADEMIC ACHIEVEMENT AND CREATIVE THINKING SKILLS OF CHEMISTRY STUDENTS IN ANAMBRA STATE, NIGERIA (UNIZIK Journal of STM Education, 2022)
This study investigated the effect of differentiated science inquiry (DSI) on academic achievement and creative thinking skills of chemistry students in Anambra State. To achieve the purpose of the study, two research questions were drawn and three hypotheses formulated and tested at 0.05 level of significance. The study adopted quasi experimental design. The population of the study was all the SS3 chemistry students in Aguata education zone totaling 2,278 students from 60 public schools in the zone. Multi-stage sampling procedure was used to obtain 72 (SS3) senior secondary III chemistry students. Two intact classes made up the sample. By a throw of coin, one intact class of 37 was used as control group while the other of 35 was used as the experimental group. The experimental group was taught using DSI while the control group was taught using lecture method of instruction. Chemistry Achievement Test (CAT) and Creative Thinking Skill Test (CTST) were used to collect the data for the study. The instruments were validated by experts and their reliability was established at 0.89 and 0.97 respectively. The data obtained for the study were analyzed using mean and standard deviation to answer the research questions and analysis of covariance (ANCOVA) wa2s used to test the hypotheses at 0.05 level of significance. The findings revealed that differentiated science inquiry teaching method was more effective in enhancing students’ academic achievement and creative thinking skills in chemistry than lecture method of instruction. There was significant difference in the creative thinking skill of the male and female students taught chemistry using differentiated science inquiry. There was improvement in the creative thinking skill for the male students than that of the female students taught chemistry using differentiated science inquiry. The study also revealed that there was no significant interaction effect of gender and teaching method on students’ creative thinking skill. Based on the findings, recommendations were made among which are chemistry teachers should adopt the use of differentiated science inquiry in their classroom instruction in order to enhance students’ academic achievement and creative thinking skill in the subject.
Keywords: Differentiated Science Inquiry; Science Inquiry; Creative Thinking; Creative Thinking Skills; Academic Achievement